1997
DOI: 10.1139/m97-081
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial endophytes in cotton: mechanisms of entering the plant

Abstract: Investigations were conducted to determine how a systemic plant-colonizing bacterium Enterobacter asburiae JM22 enters cotton plant tissues. Passive uptake was excluded for JM22 by experimentation with glutaraldehyde-fixed (killed) bacterial cells applied to seeds and leaves; no bacteria were found internally or externally on roots or leaves. In contrast, application of live JM22 cells led to colonization of external and internal root and leaf tissues. Active penetration of JM22 in the absence of external woun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0
12

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(71 citation statements)
references
References 27 publications
5
54
0
12
Order By: Relevance
“…Previous study has shown that active penetration of cotton plants by bacterial endophytes involves the hydrolysis of cellulose, which could induce systemic resistance to pathogens (30). When present within the inner tissue of asymptomatic citrus plants, C. flaccumfaciens could produce compounds or elicit some degree of enhanced resistance in these plants that leads to enhanced resistance to X. fastidiosa.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has shown that active penetration of cotton plants by bacterial endophytes involves the hydrolysis of cellulose, which could induce systemic resistance to pathogens (30). When present within the inner tissue of asymptomatic citrus plants, C. flaccumfaciens could produce compounds or elicit some degree of enhanced resistance in these plants that leads to enhanced resistance to X. fastidiosa.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that Enterobacter asburiae is a competitor of S. enterica serovar Newport and E. coli O157 on A. thaliana is indicated by the observation that its appearance on the plant was correlated with the highest competition against S. enterica serovar Newport and E. coli O157:H7. Enterobacter asburiae has been reported to be an endophyte and a frequent inhabitant of the rhizosphere of cotton, bean, and cucumber (23,24,39) and to move systemically in the plant (46). Evidence that Enterobacter asburiae inhabits the phyllosphere has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial endophytic bacteria may mediate plant adaptation to the environmental stress [53]. PGPR endobacteria alleviate plant stress due to temperature, drought, heavy metal accumulation and solar ultraviolet-B radiation (280-315 nm) [54].…”
Section: Plant Stress Tolerancementioning
confidence: 99%